Production Engineering and Management
The University of Trieste (Università degli Studi di Trieste) and the Ostwestfalen-Lippe University of Applied Sciences introduced the International Double Degree Master Program ‘Production Engineering and Management’ in 2011. Its aim is to give students in Italy and Germany, along with other countries, the chance to learn the necessary abilities from lecturers and each other. This Master Program has been accompanied by the International Conference ‘Production Engineering and Management’ from the very beginning. The annual International Conference on Production Engineering and Management took place for the fifth time this year, and can therefore be considered a well-established event originating from the partnership between the University of Trieste (Italy) and the Ostwestfalen-Lippe University of Applied Sciences (Germany). The main aim of the five conferences has been to bridge the gap between production engineering and management theory and practice, by offering a platform where academia and industry could discuss practical and pressing questions. In this respect, the fifth conference (PEM 2015) continues along the same path of the first four successful conferences, which were held in Pordenone (2011), Lemgo (2012), Trieste (2013) and again in Lemgo (2014). PEM 2015 benefited further from contributions from other universities and from research and industry projects. Especially the contributions of successful graduates of the double degree Master’s program Production Engineering and Management and those of other postgraduate researchers from several European count ries have been enforced in this year. The title ‘An active interaction between university and industry’ introduced two years ago to emphasize lively cooperation proved to be more than appropriate in the conference’s main orientation: • To present current research projects and their results at a highly sophisticated scientific level • To discuss recent developments in industry and society • To bring professionals, specialists and students together • To enable professionals, lecturers and professors to exchange experiences • To familiarize young professionals and students with scientific conference procedures • To give postgraduate and Ph.D. students the chance to present a paper • To show the two partner regions’ uniqueness and performance • To attract students for an international career in the industry • To encourage students to be open-minded about different cultures, mentalities and manners PEM 2015 took place between October 1 and 2, 2015 at the University of Trieste. The program was defined by the Organizing and Scientific Committees and clustered into five scientific sessions. Both universities and their partner organizations debated on these topics by reporting their research, experiences and success stories. The scientific sessions dealt with technical and engineering issues, as well as management topics, and included contributions by researchers from academia and industry. The extended abstracts and full papers of the contributions underwent a double-blind review process. The 35 accepted presentations were assigned, according to their subject, to one of the following sessions:, ‘Industrial Engineering and Lean Management’, ‘Technology and Supporting Services for Manufacturing’, ‘Product Lifecycle, from Concept to Market and Use’, ‘Supply Chain Design and Management’ and ‘Management Practices and Methodologies’. These sessions have been carefully selected by the organizing and scientific committees and are aimed at highlighting some of the current production industry’s most discussed topics. Therefore, the articles sustainability and revolutionary developments in modern industry and cover not only production in a narrower sense, but also new aspects of: innovation and product development, of supply chains, of quality improvement. The proceedings have been drawn together to form 35 full papers of the scientific contributions. The articles were reviewed by the Scientific Committee before being accepted. As the editors of the proceedings, we would like to thank all contributors, the referees who accepted the burden of reviewing the abstracts as well as the full papers and the members of the Organizing Committee and Scientific Committee for planning such an effective conference.